Monster-in-law - Luketic, Robert 1973-; Lopez, Jennifer 1970-; Fonda, Jane 1937-; Vartan, Michael; Sykes, Wanda 1964-; Scott, Adam 1973-; Carpenter, Russell 1950-; Newman, David 1954- (New Line Platinum series., 2005)
After years of looking for Mr. Right, Charlotte 'Charlie' Cantilini finally finds the man of her dreams, Kevin Fields, only to discover that his mother, Viola, is the woman of her most unpleasant nightmares. Viola is a recently fired news anchor who is afraid she will lose her son the way she has just lost her career, Viola becomes determined to scare off her son's new fiancâee by becoming the world's worst mother-in-law.